Pengaruh Kualitas Layanan Terhadap Kepuasan Tamu Yang Menginap Di The Oasis Boutique Beach Resort And Spa Tanjung Benoa Kab. Badung - Pratiwi, A.A Sg. Istri Ratih; Jatra, I Made (E-Jurnal Manajemen, 2014)
The quality of service needed by the company, particularly in the field of hospitality services business as customer satisfaction can be based on how the services provided by the company to the customer. Customer satisfaction is a key to the success of a company. Because the higher the quality of services provided, then the customer will be more satisfied and can increase profits and create customer loyalty to stay at the hotel. The purpose of this study was to determine the effect of service quality dimensions simultaneously and partially to the satisfaction of the guests who stay at The Oasis Boutique Beach Resort Benoa district Badung. 130 respondents was selected as the study sample. Multiple linear regression analysis is used as a data analysis technique. The results showed that the quality of services consisting of tangibles, reliability, responsiveness, assurance, and empathy influence simultaneously and partially to the satisfaction of the guests who stay at The Oasis Boutique Beach Resort Benoa district Badung. Key words : tangibles, reliability, responsiveness, assurance, emphaty